26. A newborn with transient giant sep revealed during a seizure by an integrated neurophysiological monitoring. Issue 1 (January 2015) - Lori, S.; Molesti, E.; Gabbanini, S.; Bastianelli, M.; Bertini, G.; Dani, C.
<x xml:space="preserve">Abstract</x> The role of ElectroEncephaloGraphy (EEG) and Somatosensory-Evoked-Potentials (SEP) in Neonatal as well as Adult-ICU is validated. To evaluate brain-functions in newborns with high risk of encephalic damage we also proposed an Integrated Multiparametric-Neurophysiological-Assessment (IMNA) simultaneously recording VEEG, CFM, Density-Spectral-Analisys and SEPs. We describe the case of a term-newborn (Apgar- Index 6–9, pH 7, 03) in which an 1-h-IMNA was performed at 24 h from birth, to best define the encephalic damage. Results:An early encephalic ultrasound study showed only poor evidences. During IMNA baby incidentally presented short episodes of tonic–clonic motions of left arm. These clinical signs were associated with short right emispheric EEG hypovoltages while the cascade-SEPs monitoring showed a sudden transient change in voltage: right giant SEPs traces simultaneous to seizures. After phenobarbital administration seizures stopped and the right SEPs traces return to normality. An early encephalic MRI showed a right parietal ischemic lesion and also a right extracerebral hemorrhagic injury. The latest one appeared reduced in a further MRI. No further seizures were reported. 1 h-IMNA monitoring, especially cascade-SEPs, is a useful tool to perform an early evaluation and assess prognosis of neonatal hypoxic brain damage; it also allows to correlate neurophysiological parameters? trends to clinical events.